Relationship Between Nutritional Status And College Student Learning Outcomes - S, Adi; Aliriad, Hilmy; Arbanisa, Wahyu; Winoto, Ahmad (STKIP PGRI Jombang, 2023)
The purpose of this study was to determine the relationship between college students' nutritional status and learning outcomes, especially physical education in Universitas Negeri Semarang. The type of research used is correlational. The population of this study amounted to 220 college students. This study uses primary data obtained from the measurement of the nutritional status of college students and secondary data from learning outcomes of physical education students in Universitas Negeri Semarang. The data collection tool is in the form of measuring nutritional status based on body mass index. The data were analyzed by correlational statistics through a computerized process using the SPSS program. From the results of the study, it can be concluded that there is a significant relationship between nutritional status and learning outcomes for college students.